Experiences of COVID-19-Recovered Healthcare Workers in a Tertiary Hospital in the Philippines: A Mixed-Method Inquiry. (June 2022) - Carascal, Mark B.; Capistrano, Pedro E.; Figueras, Marlouie D.L.; Cataylo, Osmuniard Lanz Angelo C.; Zuñiga, Spencer Mathew S.; Reyes, Marc Eric S.; Medriano, Kathleen Kaye S.; Gamo, Anthony T.; Mendoza, Paz D.; Macalipay, Shirley Luz B.
COVID-19 pandemic affected the mental health of the global population. Among the most vulnerable are the healthcare workers (HCWs) who got infected but returned to the frontline after recovery. Currently, there is a dearth of information and understanding on the psychological status and actual lived experience of the recovered HCWs in the Philippines. The present study investigated the psychological status and experiences of 93 COVID-19-recovered HCWs from a tertiary hospital in the Philippines using a mixed-method approach, particularly the explanatory-sequential design. Participants completed the Impact of Event Scale-Revised, and the Depression, Anxiety, and Stress Scale-21 in the quantitative phase. Selected participants took part in focus group discussions in the qualitative phase. Integrated results showed that our participants experienced significant COVID-19-related distress (mean IES-R score = 25.5; partial impact), anxiety (mean subscale score = 7.4; mild), and depression (mean subscale score = 8.1; mild). Certain sociodemographic and professional characteristics and the length of quarantine days appear to affect the psychometric scores. The quantitative results are supported by the participant's description of recovery experiences as living in uncertainty, distress, fatigue, dissociation, and valuation of life. In summary, adequate psychological support and intervention program should be prioritized and provided by hospital management for recovered HCWs to prevent the development of more serious mental health concerns that may significantly affect their tasks in caring for patients and in-hospital management.